‘I, the Implacable I’: l’opera di Joan Didion negli anni settanta (ENTHYMEMA, 2012)
This essay attempts to read Joan Didion’s work in the 1970s (Play It As It Lays, A Book of Common Prayer and The White Album) as resulting from an increasingly sharp aesthetic awareness of the modes, limits and possibilities of literature as personal and political testimony. Claiming a sceptical attitude towards any given ideology, Didion places her two novels (Play It As It Lays, A Book of Common Prayer) and non-fiction book (The White Album) within the history of that decade as filtered through an overtly autobiographical and idiosyncratic story. Out of a personal experience and understanding of that decade – of its collective imagination, its shared or unshared events and symbols – as one dominated by a sense of loss Didion creates women characters who survive both the ‘abject’ of their female bodies and the irreversible impoverishment of the last (and lost) frontiers in which their stories are set. Late-modern versions of a long-abiding and well-established American literary tradition, the character-narrators of Play It As It Lays, A Book of Common Prayer and the witness-persona of The White Album respond to Didion’s aesthetic insight into the testimonial mode, its limits and potentialities, and a narratological strategy which, not unlike the postmodern narratives of the same decade, moves toward the dissolution, scattering, and reassembling of narrative functions (author, narrator, character, and reader).
Keywords: Joan Didion; anni Settanta; New Journalism; corporeo femminile; scrittura testimoniale